Terrestrial Spaceflight Analogs: Antarctica - Crucian, Brian (2013)
Alterations in immune cell distribution and function, circadian misalignment, stress and latent viral reactivation appear to persist during Antarctic winterover at Concordia Station. Some of these changes are similar to those observed in Astronauts, either during or immediately following spaceflight. Others are unique to the Concordia analog. Based on some initial immune data and environmental conditions, Concordia winterover may be an appropriate analog for some flight-associated immune system changes and mission stress effects. An ongoing smaller control study at Neumayer III will address the influence of the hypoxic variable. Changes were observed in the peripheral blood leukocyte distribution consistent with immune mobilization, and similar to those observed during spaceflight. Alterations in cytokine production profiles were observed during winterover that are distinct from those observed during spaceflight, but potentially consistent with those observed during persistent hypobaric hypoxia. The reactivation of latent herpesviruses was observed during overwinter/isolation, that is consistently associated with dysregulation in immune function.